Reading practices in Ph. D. education programs (Islas, 2022)
Introduction: This article presents the first results of doctoral research about scientific literacies in an educative research community. The study was made in three Ph. D. programs in education and enhance the New Literacies Studies framework and intercultural education.Methods: The analysis uses a collaborative ethnographic approach and deep interviews about literacy development in this first formative trajectory. The reading practices identified and analyzed collect the first semester of studies.Results: The results point out the diverse literacies practices appropriation build in formal and non-formal educational context, characterized by a resignification of previous reading knowledge focused now on public demonstrations. Conclusions: During this process, emerge a collective sense of reading link by diverse educative research topics, condensed with uses of text that the community dispose in different formative moments.
Keywords: reading specialized practices; diverse literacies; educational research; ethnography